Seaweed Bioactivity: Effects on glucose liberation - Nazikussabah, Zaharudin (University of Copenhagen, 2017)
Hyperglycaemia (high blood sugar levels) is one of the risk factor of type 2 diabetes (T2D) when it is sustained over a longer period of time. Various factors that can lead to high blood glucose levels include glucose absorption by the small intestine and the production of glucose by liver cells. Maintenance of normal plasma glucose concentration is essential for the human health. Diet and exercise play important role to control blood sugar level. Limiting intake of high Glycaemic Index (GI) foods as part of a balanced diet is known to be important. In addition, having the right food intake such as functional foods that affect the blood sugar increase, e.g by containing inhibitors of α-amylase and/or α-glucosidase, may also help lowering the average blood sugar levels. Thus, such foods may in theory help to lower blood glucose postprandially and could potentially help delay the development of T2D in subjects with impaired glucose tolerance who regularly consumes starchy foods. The present study involved the investigation of crude extracts of dried edible seaweeds in inhibiting the carbohydrate digestive enzymes, α-amylase and α-glucosidase. Bioactive compounds from selected edible seaweeds that inhibit α-amylase and α-glucosidase were identified. The edible seaweeds that were showing high potential for inhibiting the enzymes were selected to investigate their effect on the postprandial blood glucose and insulin levels following a starch load in a human meal study.